Reverse electrodialysis salinity gradient power potential of treated municipal wastewaters used as diluted solution - Zoungrana, Ali; Aksel, Cagla; Turk, Oruc Kaan; Cakmakci, Mehmet (INDERSCIENCE ENTERPRISES LTD, 2021)
The reverse electrodialysis (RED) process fed with natural solutions was operated for six days and resulted to power densities for the combination ultrafiltration (UF) effluent-seawater, membrane bioreactor (MBR) effluent-seawater, advanced biological treatment (ABT) effluents-seawater around 0.52, 0.50 and 0.48 W.m(-2), respectively, while the synthetic solutions generated 0.57 W.m(-2). No significant difference between the power densities of synthetic and natural solutions was observed, due to their quality. The SEM-EDX analysis showed that Mg2+ and Ca2+ were present in natural solutions and may have contributed to reducing the power output. The SEM and FTIR results revealed a slight deposition of pollutants on the ions exchange membranes (IEMs) surface, but no fouling, scaling or structural modification was observed. Treated municipal wastewater discharged into seawater are important sources of energy with RED, however, high solution quality together with improved, highly selective and cost-effective IEMs are necessary to enhance and optimise the power output.
Keywords: ions exchange membranes; IEMs; reverse electrodialysis; RED; salinity gradient power; seawater; wastewater; EXCHANGE MEMBRANES; ENERGY; PERFORMANCE; GENERATION; WATER; Environmental Sciences & Ecology